Development of novel value added products from tender coconut (cocos nucifera L.) - Archana Unnikrishnan (Department of Post Harvest Technology, College of Horticulture, 2018)
The study titled ‘Development of novel value added products from tender coconut (Cocos nucifera L.)’ was carried out in the Department of Post Harvest Technology, College of Horticulture, Vellanikkara during 2016-2018. The immature nut known as tender coconut, contains a sterile liquid which is the endosperm and it has got many health benefits and medicinal values. But the popularisation of tender coconut based products is limited because of the loss in natural freshness unless treated scientifically. Therefore, an attempt was made to prepare some novel value added products from tender coconut and to evaluate their quality and shelf life. Fresh tender coconut of about 7 months maturity (cv. COD) was procured from different localities of Thrissur district. In the first experiment, RTS beverage was prepared with tender coconut and the beverage was added with 100 ppm ascorbic or malic acid in combination with one of the three preservatives, viz. potassium metabisulphite, sodium benzoate and potassium sorbate at a concentration of 100 ppm. The RTS beverage stored under refrigerated condition gave significantly longer shelf life as compared to samples stored under ambient condition. The treatment T1 (tender coconut RTS beverage added with 100 ppm ascorbic acid and 100 ppm potassium metabisulphite) gave the maximum shelf life of 25 days under ambient condition and 50 days under refrigerated storage. The same treatment was also superior with regard to titratable acidity (0.217 %), ascorbic acid (53.00 mg 100g-1), protein content (0.053 %), non-enzymatic browning (0.03), overall acceptability score (7.4) and microbial load among the treatments under refrigerated condition. Tender coconut was blended with fruit juice/pulp of guava, pineapple and sweet orange in different proportions (90:10, 80:20, 70:30, 60:40, 50:50 v/v) and based on the organoleptic score obtained for each blend, best type of tender coconut- fruit juice blend was identified. Tender coconut blended with guava pulp in 80:20, tender coconut and pineapple in 50:50 and tender coconut with sweet orange in 60:40 proportion was selected for storage studies. Tender coconut RTS beverage blended with pineapple (T2) gave significantly longer shelf life (40 and 73 days) under ambient and refrigerated storage conditions respectively. The biochemical parameters such as highest TSS (14.23o brix) and total sugar content (14.58 %), lowest non-enzymatic browning (0.03) was observed in T2 (tender coconut RTS beverage blended with pineapple) and T3 (tender coconut RTS beverage blended with sweet orange) retained highest vitamin C content (47.66 mg 100 g-1), 30 days after storage, under refrigerated condition when compared to ambient condition. Sixty days after storage, the biochemical parameters such as TSS, sugars, pH, protein and overall acceptability score was highest in T2 (tender coconut RTS beverage blended with pineapple) under refrigerated condition. Tender coconut jelly was preapared from tender coconut by incorporating jellifying agents such as agaropectin, banana peel pectin, guava pectin and nutmeg rind pectin at different concentrations (0.5 %, 1.0 %, 1.5 % and 2 %). Treatments such as C3 (1.5 % agaropectin), C4 (2 % banana peel pectin), C3 (1.5 % guava pectin) and C4 (2 % nutmeg rind pectin) showed highest overall acceptability score of 7.5, 7.5, 7.2 and 7.5 respectively. Tender coconut jelly could be stored for 73 days under ambient condition whereas under refrigerated condition, the shelf life beyond 90 days. T4 (tender coconut jelly prepared from nutmeg rind pectin) showed lowest (0.75) water activity Highest vitamin C (11.93 mg 100 g-1) was observed in T3 (tender coconut from guava pectin) under both refrigerated storage conditions. Tender coconut jelly from nutmeg rind pectin (T4) showed highest overall acceptability value of 7.7 and 7.4, 2 months after storage under ambient condition and 3 months after storage under refrigerated condition respectively. The results of the study indicated that through scientific handling along with addition of preservatives, the tender coconut can be utilized as a potential source for the production of many novel value added and processed products.